Japanese herbal medicines shosaikoto, inchinkoto, and juzentaihoto inhibit high‐fat diet‐induced nonalcoholic steatohepatitis in db/db mice. (17th September 2014) - Takahashi, Yoshihisa; Soejima, Yurie; Kumagai, Arisa; Watanabe, Masato; Uozaki, Hiroshi; Fukusato, Toshio
<x xml:space="preserve">Abstract</x> Few studies have investigated the effects of Japanese herbal medicines on nonalcoholic fatty liver disease (NAFLD)/nonalcoholic steatohepatitis (NASH). To the best of our knowledge, only one study has examined whether high‐fat (HF) diet‐fed db/db mice are appropriate animal models of NASH. We investigated the effects of four types of Japanese herbal medicines (shosaikoto (TJ‐9), inchinkoto (TJ‐135), juzentaihoto (TJ‐48), and keishibukuryogan (TJ‐25)) on hepatic lesions of HF diet‐fed db/db mice. Db/db mice were divided into six groups: control diet (control); HF diet (HF); and HF diet supplemented with TJ‐9, TJ‐135, TJ‐48, or TJ‐25 (TJ‐9, TJ‐135, TJ‐48, and TJ‐25, respectively). Mice were killed after 6 weeks of treatment, and biochemical and pathological analyses were performed. Mice in the HF group consistently developed histopathological features consistent with definite NASH, and marked necroinflammation occurred. Serum alanine aminotransferase levels in the TJ‐9, TJ‐135, and TJ‐48 groups were significantly improved compared with those in the HF group. With regard to liver histology, TJ‐9 and TJ‐48 significantly improved lobular inflammation, and TJ‐135 significantly improved ballooning degeneration. We have shown that HF diet‐fed db/db mice are animal models that correctly recapitulate the histopathology of human NASH and that TJ‐9, TJ‐135, and TJ‐48 inhibit necroinflammatory activity in this model.